Tünde A. Barabás Settlement Instead of Prison? Mediation and Other Alternative Sanctions in Europe (Academic Journal of Internal Affairs, 2013)
The author presents Tünde A. Barabás's book "Settlement instead of Prison?", which examines the criminal procedure from the victim's point of view, but it is definitely the most complete and comprehensive of her works on the subject. The book deals with an increasingly prominent legal institution, mediation, i.e. the criminal policy problems of victim-offender mediation.
Keywords: mediation; victim-offender; justice